2016
DOI: 10.1136/bmjopen-2016-012602
|View full text |Cite
|
Sign up to set email alerts
|

Does ‘existential unease’ predict adult multimorbidity? Analytical cohort study on embodiment based on the Norwegian HUNT population

Abstract: ObjectivesMultimorbidity is prevalent, and knowledge regarding its aetiology is limited. The general pathogenic impact of adverse life experiences, comprising a wide-ranging typology, is well documented and coherent with the concept allostatic overload (the long-term impact of stress on human physiology) and the notion embodiment (the conversion of sociocultural and environmental influences into physiological characteristics). Less is known about the medical relevance of subtle distress or unease. The study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…179,180,181,182,183 There is also evidence that poor mental health and psychosocial risk factors such as feeling dissatisfied with life, not feeling calm, having sleep problems that affect work, and financial concerns are predictive of multimorbidity in various age groups. 184,185 Other evidence has similarly shown that living in a family compared to living alone, and being part of a large social network, are protective factors for multimorbidity occurrence. 186 The relationship between mental health and physical conditions is complex, but appears to be bidirectional and may arise due to shared biological factors, or mediated by various lifestyle and treatment specific factors.…”
Section: Co-existing Mental and Physical Health Multimorbiditymentioning
confidence: 99%
“…179,180,181,182,183 There is also evidence that poor mental health and psychosocial risk factors such as feeling dissatisfied with life, not feeling calm, having sleep problems that affect work, and financial concerns are predictive of multimorbidity in various age groups. 184,185 Other evidence has similarly shown that living in a family compared to living alone, and being part of a large social network, are protective factors for multimorbidity occurrence. 186 The relationship between mental health and physical conditions is complex, but appears to be bidirectional and may arise due to shared biological factors, or mediated by various lifestyle and treatment specific factors.…”
Section: Co-existing Mental and Physical Health Multimorbiditymentioning
confidence: 99%
“…In Iceland, multimorbidity (2+ conditions) prevalence was estimated at 35% using primary care data (n = 221,822) [14]. Analysis of a prospective rural northern cohort in Norway identified multimorbidity (2+ conditions) prevalence of 30.8% (n = 20,365) [15]. In Sweden, a study including people ages 77 to 100 years (n = 1,099) found a prevalence of multimorbidity (2+ conditions) of 55%.…”
Section: Discussionmentioning
confidence: 99%
“…Canadian studies have produced evidence regarding these risk factors for multimorbidity, and have highlighted the role of socioeconomic disparities in multimorbidity [3,[11][12][13]. Other circumpolar countries have investigated multimorbidity prevalence, patterns, predictors, and prescribing practices, with varying results, and prevalence estimates ranging from 21.6% to 55%, depending on participants, data source, and included conditions [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of allostatic load gives, by measuring psychophysiological stressors, a quantifiable measure of the pressure put on regulatory systems in the body striving to uphold equilibrium or homeostasis. The concept encompasses the concept of embodiment, how sociocultural and environmental influences translate to the human body) [ 32 ]. Researchers conclude: “It is becoming increasingly clear how subtle yet longstanding challenges impact on the human physiology and predispose to disease…likewise, it is acknowledged that it is subjective experience, not objectively quantifiable events, that becomes biologically inscribed.” [ 32 ].…”
Section: Discussionmentioning
confidence: 99%